Y1, C8 - Proof by Induction Flashcards
What are the steps for a general proof by induction
1) Base case- n = 1 and solve
2) Assumption- n = k and assume correct
3) Inductive case- n = k + 1
4) Conclusion- Write sentence proving is it true
What should the conclusion step say
Since true for n = 1 and if true for n = k, true for n = k + 1. Therefore true for all n
How do you do summation proof
1) Write out LHS and RHS for n = 1 and show they are equal
2) Write out LHS and RHS for n = k and assume true
3) Write out LHS and RHS for n = k + 1, splitting the summation from r = 1 to k and then adding the function of (k + 1)
4) Sub in your known value of the sum of n = 1 to k and solve
5) LHS should then equal RHS for n = k + 1
6) Conclusion step
How would you split the sum of (2r - 1) from n = 1 to k +1
(The sum of (2r - 1) from n = 1 to k) + (2(k+1) - 1)
How to sub in n = k + 1 for a summation
Split the summation into form r = 1 to n = k + (the function of (k + 1))
How to solve divisibility proof by inductions
1) Solve for n = 1
2) Assume n = k
3) f(k + 1) - f(k)
Simplify
Get into form polynomial + f(k) = f(k + 1) where the polynomial is divisible by the required integer
4) Polynomial is divisible and we know f(k) is divisible therefore true for all +ve integers
Prove by induction that n^3 - 7n + 9 is divisible by 3 for all positive integers n
1) n = 1 –> 1 - 7 + 9 = 3
2) n = k –> k^3 - 7k + 9 assume divisible by 3
3) n = k + 1 –> (k + 1)^3 - 7(k + 1) + 9
–> k^3 + 3k^2 + 3k + 3
f(k+1) - f(k) = k^3 + 3k^2 + 3k + 3 - (k^3 - 7k + 9) = 3k^2 + 3k + 6
Therefore f(k+1) - f(k) = 3(k^2 + k + 2) and so f(k+1) = 3(k^2 + k + 2) + f(k) which is all divisible by 3
Prove by induction that 8^n - 3^n is divisible by 5
1) n = 1
2) n = k –> 8^k - 3^k
3) f(k+1) - f(k) –> 8^k+1 - 3^k+1 - (8^k - 3^k)
8 * 8^k - 3 * 3k - 8^k + 3^k
7 * 8^k - 23^k
= 5 * 8^k - 23^k + 2 * 8^k
= 5 * 8^k + 2(8^k - 3^k)
Therefore f(k+1) - f(k) = 58^k + 2f(k)
And so f(k+1) = 5*8^k + 3f(k) which is all divisible by 5
How do you do matrix proofs by induction
1) n = 1
2) Assume n = k for LHS = RHS
3) n = k+1, write out LHS and RHS (aim)
4) Split the matrix to have it in the form matrix^n + matrix
5) Sub in known result for M^k and multiply the matrices so they equal the RHS (aim)
6) Conclusion
Which type of proof by induction isn’t in the specification
Recurrence relation proofs
How do you do recurrence relation proofs (1 assumption)
1) n = 1
2) n = k, write out LHS and RHS
3) n = k+1, write out LHS and RHS (aim)
4) Sub in u(k) into formula for u(k+1) and solve through so LHS = RHS (aim)
5) Conclusion
How do you do recurrence relation proofs (2 assumptions)
1) n = 1, check true
2) n = 2, check true
3) n = k, write out LHS and RHS and assume true
4) n = k+1, write out LHS and RHS and assume true
5) n = k+2, write out LHS and RHS (aim)
6) Sub in u(k) and u(k+1) into formula for u(k+2) and solve through so it equals RHS (aim)
7) Conclusion
How would you write 3^k+1 in the form of k * 3^k-2 where k is a constant
k = 27
27 * 3^k-2 = 3^k+1